Using Acridine Orange Dye/ PVA Composite Films for Flexible Laser Filters - Debopriyo Ghoshal (AG Volumes, 2022)
Dye/polymer composite has risen as one of the most important segments of optoelectronics due to their excellent optical, mechanical and electrical properties. Dye loaded polymer materials have drawn tremendous attention in recent times due to its unique combination of electrical and optical properties and wide range of applications in different fields. In this work, the primary intension is to synthesize flexible, economic, non-toxic, highly durable and chemically stable dye loaded PVA self-standing films and to observe how it’s structural, morphological, optical and electrical properties influence the laser filtering properties of the films. Here we study the structural, optical and electrical properties of the low-cost Acridine orange (AO)/poly (vinyl alcohol) (PVA) composites (AO concentration 0wt%, 1.0wt%, 2.0wt %) arranged by simplistic solution casting technique. A considerable change in the band gap is also observed for the 2.0% AO/PVA composite ( 1.8eV) than that of the neat PVA ( 4.7eV). A 2.0wt% AO/PVA film of width 350 ± 25 μm can fully block electromagnetic irradiation in the 200-540nm wavelength region and can successfully block high power laser (1.5mW) of wavelength ̴ 544 nm.